2006
DOI: 10.1007/s00101-006-1064-x
|View full text |Cite
|
Sign up to set email alerts
|

Die neuen Reanimationsleitlinien 2005 des European Resuscitation Council

Abstract: The new CPR guidelines are based on a scientific consensus which was reached by 281 international experts. Chest compressions (100/min, 4-5 cm deep) should be performed in a ratio of 30:2 with ventilation (tidal volume 500 ml, Ti 1 s, FIO2 if possible 1.0). After a single defibrillation attempt (initially biphasic 150-200 J, monophasic 360 J, subsequently with the respective highest energy), chest compressions are initiated again immediately for 2 min. Endotracheal intubation is the gold standard; other airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 172 publications
0
1
0
5
Order By: Relevance
“…Although one case study showed initiation of torsades de pointes during TTM due to a QTc of 726 milliseconds, several studies have shown that QTc prolongation during TTM has no effect on the potentiation of fatal arrhythmias; however, they do not describe QTc intervals greater than 700 milliseconds. TTM has become the standard of care per all current major critical care guidelines including those from the International Liaison Committee on Resuscitation [ 11 ] and the European Resuscitation Council [ 12 ]. However, no guidelines exist regarding EKG monitoring during TTM, nor are there recommendations describing when TTM should be stopped in association with QTc prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Although one case study showed initiation of torsades de pointes during TTM due to a QTc of 726 milliseconds, several studies have shown that QTc prolongation during TTM has no effect on the potentiation of fatal arrhythmias; however, they do not describe QTc intervals greater than 700 milliseconds. TTM has become the standard of care per all current major critical care guidelines including those from the International Liaison Committee on Resuscitation [ 11 ] and the European Resuscitation Council [ 12 ]. However, no guidelines exist regarding EKG monitoring during TTM, nor are there recommendations describing when TTM should be stopped in association with QTc prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…B. während kurzer Phasen von ROSC (return of spontaneous circulation; Wiederherstellung eines Spontankreislaufs) -gezielt auf infarkttypische Veränderungen geprüft werden. Sowohl bei LE als auch bei AMI ist die medikamentöse Thrombolyse als klinische Routinetherapie nicht mehr wegzudenken und wird auch in den aktuell gültigen Leitlinien der European Society of Cardiology (ESC) und des European Resuscitation Councils (ERC) empfohlen [18]. In der Notfallmedizin hingegen galt die Thrombolyse lange Zeit als umstritten [19][20][21][22][23] und teilweise sogar als kontraindiziert [24] aus Sorge vor unbeherrschbaren BluObwohl die Thrombolyse während CPR momentan keine Standardtherapie darstellt, sollte sie leitlinienkonform bei hochgradigem Verdacht auf eine zugrunde liegende fulminante Lungenembolie sowie darüber hinaus in begründeten Einzelfällen dem Patienten nicht vorenthalten werden.…”
Section: Myokardinfarktunclassified
“…Sowohl bei LE als auch bei AMI ist die medikamentöse Thrombolyse als klinische Routinetherapie nicht mehr wegzudenken und wird auch in den aktuell gültigen Leitlinien der European Society of Cardiology (ESC) und des European Resuscitation Councils (ERC) empfohlen [40]. In der Notfallmedizin hingegen galt die Thrombolyse lange Zeit als umstritten [6,13,26,27,35] und teilweise sogar als kontraindiziert [31] aus Sorge vor unbeherrschbaren Blutungskomplikationen.…”
Section: Myokardinfarktunclassified